Effects of non-audit services on professionalism: case of PKF chartered accountants Zimbabwe - Magama, Isheanesu (2017)
The Zimbabwean audit industry has been agonised by compromised auditor professionalism as a result of the joint provision of non-audit services and audit services. Based on this background, this study endeavours to investigate the effects of non-audit services on professionalism. A quantitative method and descriptive approach was adopted for the presentations and analysis of data and a review of literature of various scholars who also investigated auditor professionalism and non-audit service was conducted. A sample size of 35 employees (65) was used for the gathering of data used in this study. The results advocate that NAS provision affect professionalism though there is need to salvage its provision due to other positive effects.